FOCALIZATION ANALYSIS APPLIED IN THE PRINCESS BRIDE MOVIE - Muhammad Rizal; Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2021)
This study aims to answer the statement of the problems: (1) what kind of point of view is used in the movie entitled “The Princess Bride”, (2) What kind of focalization is used in “The Princess Bride movie”, (3) How does the narrator know everything regarding the story. The researcher uses theory by Genette (1980) and the researcher uses qualitative method. The result of the analysis showed that: (1) this movie uses third-person perspective in the movie because the narrator uses nominative form and accusative form in the movie, (2) the researcher found that the narrator as omniscient narrator, this is indicated that this movie used zero focalization because the narrator knows everything regarding in the movie such as the main character feelings and activities in the movie and the narrator also knows the minor character feelings, past, and activities in the movie. Keywords: point of view, focalization, omniscient narrator, Genette, The Princess Bride